GENETIC ANALYSIS OF Bidens pilosa THROUGH RAPD TECHNIQUE - VIDAL, Ribas Antonio; NUNES, Anderson Luis; RESENDE, Luciane Vilela; LAMEGO, Fabiane Pinto; SILVA, Paulo Roberto da (Scientia Agraria, 2007)
Reduced genetic similarity in Bidens pilosa, due to a significant outcross rate favors natural selection of genotypes resistants to herbicides used for control. The objective of present work was to determine the genetic similarity between resistant and susceptible biotypes to herbicides inhibitors of the ALS enzyme. Seeds were collected in Paraná and Rio Grande do Sul States and sowed in the greenhouse at Federal University in Rio Grande do Sul, during 2004. Through the technique of Random Amplified Polymorphic DNA (RAPD), it was possible to evaluate genetic differences among Bidens biotypes. All primers amplified and showed good band reproducibility. The average coefficient of genetic similarity was 43%. The low genetic similarity observed among ALS-resistant and susceptible accesses suggests that the occurrence of resistant genotypes is due to natural selection, acting on a wide spectrum of different genotypes: reduced genetic similarity linked to high genetic variability, caused by significant outcrossing rate.